Treating intrahepatic cholangiocarcinoma with pemigatinib: two case reports of Nordic patients - Vesa T. Väliaho; Iben Spanggaard (Acta Oncologica)
Background: Cholangiocarcinoma (CCA) is a diverse group of aggressive liver tumors with up to 20% being intrahepatic CCA (iCCA). Up to 15% of patients with iCCA have fibroblast growth factor receptor 2 (FGFR2) fusions or rearrangements. Here we evaluated iCCA treatment with pemigatinib, a selective inhibitor of FGFR1–3, in two patients from Denmark and Finland.